A Split Face Comparative Study Of Microneeding With Platelet Rich Plasma Versus Fractional Co2 Laser With Platelet Rich Plasma In Management Of Atrophic Acne Scars (Indian Journal of Applied-Basic Medical Sciences, 2020)
Introduction: Acne scars, a disfiguring malady is a challenge for dermatologists, despite  having multiple treatment modalities like subsicion, microneedling, dermabrasion, TCA  CROSS, Fractional CO2 Laser, dermal fillers, etc. However, monotherapy has been hardly  satisfactory because of the polymorphism seen with the scars. Platelet Rich Plasma (the  autologous plasma with high concentration of platelets) has been versatile since its advent.  It has been revolutionary in the management of acne scars by providing numerous growth  factors aiding in scar remodelling along with time proven methods. Materials & Methods: A prospective analytical study was conducted over a period of 6  months including 26 patients. Each patient received microneedling plus PRP on right side of  the face while Fractional CO2 Laser plus PRP on the left side simultaneously for total 6 such  sittings at 21 days interval. Response was noted with serial photographs and goodman’s  qualitative and quantitative scores. Autologous PRP was prepared with double spin method  to yield uniformly high amount of platelets. Results: Out of 26 patients enrolled in the study, none of the patient reported a poor  response which means both the modalities are effective. The Average Qualitative score, pre  and post treatment showed significant difference with 10 patients showing excellent results  in Fractional CO2 Laser treated side. Conclusion: Fractional CO2 Laser is a non invasive procedure with PRP boosting the end  results in acne scar treatment, hence should be considered one of the first line treatments.
Keywords: Acne Scars; Microneedling; Fractional CO2 Laser; PRP